Training of information security undergraduate in the education mode of cyberspace security - Ruiying DU; Huanguo ZHANG; Jianming FU; Jing CHEN; Ming TANG; Kun HE; Dan LIU; Yongping DAI (网络与信息安全学报)
How to ensure quality of information security undergraduate training under the mode of general education was discussed.Based on the in-depth analysis of the characteristics and knowledge structure of information security specialty,some targeted solutions were put forward,such as the integration of specialized courses,the cultivation of security thinking,and the Internet + flipped classroom teaching mode.